Understanding the effect of gloves on hand-arm vibrations in road cycling - Sanseverino, G.; Schwanitz, S.; Krumm, D.; Odenwald, S.; Lanzotti, A. (Proceedings, 2020)
The aim of this research was to study the effects of cycling gloves on hand-arm vibrations in realistic load scenarios. A test has been performed in the laboratory, a road bicycle handlebar was mounted to the hydraulic cylinder of a universal testing machine, and the bicycle was fixed on an indoor trainer. Tests were executed for three different hand sizes (small, medium, large), three different frequency ranges (15-25, 35-45, 85-95 Hz), with two different types of gloves (gel-padded; non-padded) and without gloves. The amplitudes and each frequency bands were obtained from a previous field test. Hand-arm vibrations were quantified by means of root mean square values of the frequency-weighted accelerations measured at the subject`s wrist joint. Analysis of variance (ANOVA) showed no significant effect of gloves in reducing vibration transmissibility.